An Android Application to Secure Text Messages - Demirol, Doygun; Das, Resul; Tuna, Gurkan (Ieee, 2017)
For mobile phone users, short message service (SMS) is the most commonly used text-based communication type on mobile devices. Users can interact with other users and services via SMS. For example, users can send private messages, use information services, apply for a job advertisement, conduct bank transactions, and so on. Users should be very careful when using SMS. During the sending of SMS, the message content should be aware that it can be captured and act accordingly. Based on these findings, the elderly, called as Silent Generation which represents 70 years or older adults, are text messaging much more than they did in the past. Therefore, they need solutions which are both simple and secure enough if there is a need to send sensitive information via SMS. In this study, we propose and develop an android application to secure text messages. The application has a simple and easy-to-use graphical user interface but provides significant security.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Elderly; Communication; Text Messages; Confidentiality